Guayaquil Metropolitano - Mancero, Rocio (Revista Universidad de Guayaquil, 1998)
The objective of this exercise on the vision of engineering in the future is to propose physical, strategic, social, and economic guidelines to guide its development, presenting some ideas that can be tried in order to build a new and better 21st century in Guayaquil with our technical responsibilities.Guayaquil is a heterogeneous and diverse city that is constantly changing, covering an urban area of 33,000 hectares, according to the official register of December 19, 1991, and with the specific characteristics of each of the Municipal Planning areas established in Official Register #864 of 1995.